Reflective writing: I wouldn't start from here – examining a professional development initiative to enhance the scholarly activity of English HE in FE lecturers. Issue 4 (3rd July 2016) - McKenzie, Liz; Turner, Rebecca; Gale, Ken
Abstract: This paper explores the nature of reflective writing through the experience of the researchers in running a series of writing workshops with a group of higher education practitioners working in a UK further education college. The focus here is on reflective writing, which was chosen to start the sequence of workshops, as it was perceived as a form of writing with which the participants would be familiar, given its role in the education and development of teachers within the sector. Our assumption was that this familiarity would facilitate the writing process and participants would readily respond by engaging in reflective writing. However, in practice this proved not to be the case, despite being introduced to a variety of different forms of writing over a series of workshops, it took the participants longer than we expected to begin to write. This led us to question our assumptions about the starting point for the writing workshops and what they might achieve. The paper draws on field notes made during the writing initiative and data gathered through focus groups and interviews with the participants, as well as extracts of their writing to examine their experiences. Different conceptualisations of reflective writing are identified and their implications are explored in relation to the participants' engagement with writing and their experience of professional development.